Plants' ability to sense and respond to airborne sound is likely to be adaptive: reply to comment by Pyke et al. (23rd June 2020) - Goldshtein, Aya; Veits, Marine; Khait, Itzhak; Saban, Kfir; Sapir, Yuval; Yovel, Yossi; Hadany, Lilach
Abstract: Ecol. Lett. 22, 2019, 1483 demonstrated, for the first time, a rapid response of a plant to the airborne sounds of pollinators. Pyke et al . argue that this response is unlikely to be adaptive. Here we clarify some misunderstandings, and demonstrate the potential adaptive value using theoretical modelling and field observations. Abstract : In (Veits et al. 2019) we demonstrated, for the first time, a rapid response of a plant to the airborne sounds of pollinators. Pyke et al. argue that this response is unlikely to be adaptive. Here we clarify some misunderstandings, and demonstrate the potential adaptive value of plant response to sound, using theoretical modelling and field observations.